(untitled) (Global Journal of Human-Social Science, 2019)
The primary quest of humanity is for happiness and the meaning of life. Most people throughout life remain unaware of the ’individual self,’ the foundation of one’s identity, and tread on the known ways of the society to make life meaningful. Consequently, the ’being’ of such a person fails to come to existence. Only a few are ever able to become conscious of this ’self’ in moments of pure reflection enabled by a complete divorce from the social presence. The consciousness leads to a concurrent awareness of the meaninglessness of the world and the true concept of freedom. Freedom fetches agony with the realization of the sole responsibility of one’s choice. A person is then either on the way to construct the meaning of life and find happiness in a personalized way or get crushed at the burden of his anguish. The consciousness of the individual self, the awareness of personal freedom in a fundamentally meaningless world, and the consequence of this consciousness in both its aspects -all the facets of man’s existential problem have been portrayed in the lines of the great Bengali poet Jibanananda Das (1899 -1954) with poignancy and vividness. We can, at the same time, parallel the situation presented in his poetry with his personal life.